PENERAPAN MEDIA AUDIO VISUAL PADA MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFAE) DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN KAMULAN II KECAMATAN TALUN KABUPATEN BLITAR - Novialita Angga Wiratama (Widyagogik, 2019)
The purpose of this study is to describe the validity and reliability of science process skills based test instruments and the quality of science process skills based on test instruments is viewed from the level of difficulty, power difference, and deception in material objects and their properties for Grade V SDN 010 Tarakan. The type of research used in this research is the Formative Evaluation Research and Development design. Research Results there are 30 items in the form of multiple-choice, the initial steps are validation by a team of experts in a very feasible category. The one-to-one trial was conducted in conjunction with the validation of the one-to-one trial experts to get 90% of students' responses in the very effective category. The results of the SPSS 21 program analysis show 20 questions in the valid category, the reliability is r11 = 0.585 more than r table = 0.284. The results of the analysis of the AnatesV4 program show the level of difficulty with difficult categories of 1 item problem (3.3%), the level of difficulty of the questions that are in the easy category a number of 1 item (3.3%), the level of difficulty of the questions which are in the category of very easy number 2 items of questions (6.7%), the level of difficulty of the questions in the moderate category, 26 items of questions (86.7%), the results of the average power difference with a good criterion of 12 questions (40%), and an effective deceiver as many as 28 items (93.3%).